Face Reader Using Single Board Computer & GNU-Linux - Ali Yeon, Md. Shakaff, Prof. Dr. (Malaysian Invention and Design Society (MINDS), 2010)
Prof. Dr. Ali Yeon Md. Shakaff and his team from School of Computer & Communication Engineering and School of Mechatronic Engineering won bronze for Face Reader Using Single Board Computer & GNU/Linux. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.